Answer:
abc = - 126
Step-by-step explanation:
(2x + 3)(3x - 1) ← expand product using FOIL
= 6x² + 7x - 3 ← in standard form
with a = 6, b = 7, c = - 3
Then
abc = 6 × 7 × (- 3) = - 126
Answer:heya
Step-by-step explanation:
it is in the form... a raise to the power n / a raise to the power m = a raise to the power n-m..........
so 9 raise to the power 2/9 raise to the power 7= 9 raise to the power(2-7)
=9 raise to the power -5
=1/9 raise to the power 5
hope it helps
Answer:
22 pi ft
Step-by-step explanation:
We can use the area to find the radius
A = pi r^2
121 pi = pi r^2
Divide each side by pi
121 = r^2
Take the square root
sqrt(121) = sqrt(r^2)
11= r
Now we need to find the circumference
C = 2*pi*r
C = 2* pi *11
C = 22 pi ft
First, divide by a to get c + b = d/a. Next, subtract the b to get c = d/a - b.
Optional:
c = d/a - ba/a = (d-ba)/a
Answer:
13
Step-by-step explanation:
If the rabbit started at 10 you would add 3 to 10 and get 13.